PENYULUHAN POLA MAKAN MENGURANGI KEJADIAN KURANG ENERGI KRONIS PADA WANITA USIA SUBUR - Irni Setyawati; Dian Soekmawati Riezqy Arienda; Sri Handayani; Kusniyati Utami; Sarah Husyanti (Jurnal LENTERA, 2023)
Chronic Energy Deficiency (CED) often affects women of childbearing age. The Local Area Monitoring Report of mothers for Karang Pule Health Center in November 2021 found 5.74% (19 people out of 73 pregnant women) experienced The purpose of this service was to increase awareness and the eating behavior of women of childbearing age.The service activity "Counseling on the diet of women of childbearing age" used method which begins with identification of eating patterns and ends with an evaluation of changes in women of childbearing age weight that is carried out in the Dasan Kolo environment, Jempong Baru village. After the dedication, there was an increase in women of childbearing age weight by 1 kg at 66.67% women of childbearing age and there was 33.33% women of childbearing age weight by 2 kg at. This increase in women of childbearing age weight indicated that counseling on women of childbearing age diets was able to change the dietary behavior who experience CED. It is hoped that women of childbearing age can adopt a diet in accordance with the recommended number of servings of adequate energy and protein that has been understood. In addition, the study program can follow up by observing and evaluating the eating behavior of female students who have received this counseling.